Design and Manufacture of Number of People Counting Devices Using the AT89S52 Microcontroller - Jonas Franky Panggabean (Marqcha Institute, 2022)
In today's world all things are required to find solutions that are able to solve problems accurately and quickly. Along with the development of time, technological developments continue to move rapidly so that various tools are produced that are able to provide solutions to the difficulties faced by humans. As well as activities that occur in a room. This research helps general work, namely counting the number of people in the room automatically according to the program that we set in the AT89S52 microcontroller